2008
DOI: 10.1007/s10620-008-0482-9
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Seropositivity in Patients with Acute Coronary Syndromes

Abstract: The aim of this study was to investigate the seroprevalence of Helicobacter pylori (HP) in patients with coronary atherosclerosis and acute coronary syndromes. We enrolled 152 patients (group I, 73 patients with acute coronary syndrome; group II, 79 patients with chronic stable angina) and 22 control subjects. An enzyme-linked immunosorbent assay for immunoglobulin (Ig) G test for HP diagnosis was used on all enrolled subjects. C-reactive protein (CRP) was also measured in all patients as an inflammatory marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 18 publications
6
31
0
Order By: Relevance
“…Although it was observed an inverse relation between H. pylori infection and serum albumin, the bacteria presence was unrelated to C-reactive protein and the leukocyte count, regardless of CagA status (4) . Such result was also reported in several studies that showed no impact of H. pylori's infection in systemic markers of inflammation (13,15,36,38) . CagA is the most extensively investigated virulence factor of H. pylori being encoded by cytotoxin-associated genes pathogenicity island (cagPAI) (3) .…”
supporting
confidence: 84%
“…Although it was observed an inverse relation between H. pylori infection and serum albumin, the bacteria presence was unrelated to C-reactive protein and the leukocyte count, regardless of CagA status (4) . Such result was also reported in several studies that showed no impact of H. pylori's infection in systemic markers of inflammation (13,15,36,38) . CagA is the most extensively investigated virulence factor of H. pylori being encoded by cytotoxin-associated genes pathogenicity island (cagPAI) (3) .…”
supporting
confidence: 84%
“…Several epidemiological studies have suggested an association between H. pylori seropositivity and atherosclerosis [43] [44]. The Th1 immune response against heat shock protein 60 (HSP60) derived from pathogens is thought to be a proatherogenic process and was related to the progression of atherosclerosis in a hyperlipidemic mouse model [45].…”
Section: Bacteriamentioning
confidence: 99%
“…Substantial biological data implicate inflammatory pathways in the onset of early atherogenesis, progression of the lesions and thrombotic complications associated with this disease. Clinical investigations have confirmed correlations between circulating markers of inflammation, such as C-reactive protein (CRP) 28,71,72) , tumor necrosis factor (TNF) 73,74) , interleukin (IL)-6 71,75) and IL-18 76,77) , and the occurrence of atherosclerosis and its cerebrovascular or cardiovascular events. In addition, growing evidence suggests that H. pylori infection, accompanied by persistent low-grade systematic inflammation, contributes to the risk of atherosclerosis by stimulating the production of proinflammatory cytokines, such as CRP 78,79) , IL-6 80) , and IL-18 81) , all of which are predictors of atherosclerosis.…”
Section: H Pylori Related-inflammation and Atherosclerosismentioning
confidence: 99%